2018
DOI: 10.1038/s41418-018-0138-z
|View full text |Cite|
|
Sign up to set email alerts
|

USP20 positively regulates tumorigenesis and chemoresistance through β-catenin stabilization

Abstract: β-catenin is a major transcriptional activator of the canonical Wnt/β-catenin signaling pathway. It is important for a series of biological processes including tissue homeostasis, and embryonic development and is involved in various human diseases. Elevated oncogenic activity of β-catenin is frequently observed in cancers, which contributes to survival, metastasis and chemo-resistance of cancer cells. However, the mechanism of β-catenin overexpression in cancers is not well defined. Here we demonstrate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 76 publications
1
48
0
Order By: Relevance
“…β-catenin, a major transcriptional activator of the canonical Wnt/β-catenin signaling pathway, is important for a series of biological processes, including tissue homeostasis and embryonic development, and is involved in various human diseases. USP20 was reported to positively regulate tumorigenesis and chemoresistance through β-catenin stabilization [ 45 ]. Moreover, lncRNAs, such as the lncRNA CRNDE, were also found to regulate cancer chemo-resistance by influencing Wnt/β-catenin signaling [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin, a major transcriptional activator of the canonical Wnt/β-catenin signaling pathway, is important for a series of biological processes, including tissue homeostasis and embryonic development, and is involved in various human diseases. USP20 was reported to positively regulate tumorigenesis and chemoresistance through β-catenin stabilization [ 45 ]. Moreover, lncRNAs, such as the lncRNA CRNDE, were also found to regulate cancer chemo-resistance by influencing Wnt/β-catenin signaling [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we determined a promoting effect of miR-532-3p in CRC chemosensitivity via its inhibition of β-catenin and activation of p53. Multiple chemotherapies were verified to induce cell cycle arrest and early apoptosis by both inhibition of Wnt responsiveness and stabilization and activation of p53 32,33 . Moreover, the activation of Wnt/ β-catenin and mutation or depletion of p53 were regarded as a fundamental process of adaptive resistance in CRC 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, p0071 interacts with E-cadherin in the cytoplasm and promotes invasion and metastasis in nonsmall cell lung cancer [45]. Furthermore, ubiquitin speci c peptidase 20 (USP20) regulates the deubiquitination of β-catenin to control the invasion and migration of cancer cells [46]. Our results showed that the overexpression of mir-335-5p decreases the expression of vimentin and β-catenin and increases E-cadherin in MKN-28 and SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 76%